2016
DOI: 10.1007/s11136-016-1478-0
|View full text |Cite
|
Sign up to set email alerts
|

Cost of informal care for patients with cardiovascular disease or diabetes: current evidence and research challenges

Abstract: Purpose Patients with cardiovascular disease (CVD) or diabetes often require informal care. The burden of informal care, however, was not fully integrated into economic evaluation. We conducted a literature review to summarize the current evidence on economic burden associated with informal care imposed by CVD or diabetes. Methods We searched EconLit, EMBASE, and PubMed for publications in English during the period of 1995 to 2015. Keywords for the search were informal care cost, costs of informal care, info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
(70 reference statements)
0
18
1
Order By: Relevance
“…Aside from this study and that reported by Joo and colleagues, 18,19,43 costs of informal caregiving associated with CVD are not well documented. Our estimates of the per-person hours of informal caregiving attributable to heart failure and stroke are consistent with previous studies.…”
Section: Dunbar Et Al Costs Of Informal Caregiving For Cvdcontrasting
confidence: 56%
See 4 more Smart Citations
“…Aside from this study and that reported by Joo and colleagues, 18,19,43 costs of informal caregiving associated with CVD are not well documented. Our estimates of the per-person hours of informal caregiving attributable to heart failure and stroke are consistent with previous studies.…”
Section: Dunbar Et Al Costs Of Informal Caregiving For Cvdcontrasting
confidence: 56%
“…78 For diabetes mellitus, the estimated annual costs of caregiving were reported to range from $1162 to $5082 per person. 43 As expected, the caregiving needs of Alzheimer disease bring the highest cost compared with those of stroke, mental illness, cancer, and multiple sclerosis. 55 However, detailed comparisons with other diseases that rely on consistent methodology are lacking.…”
Section: Caregiving Costs In Noncardiovascular Chronic Conditionsmentioning
confidence: 77%
See 3 more Smart Citations